2009
DOI: 10.1111/j.1471-4159.2009.06094.x
|View full text |Cite
|
Sign up to set email alerts
|

Increases in cytoplasmic dopamine compromise the normal resistance of the nucleus accumbens to methamphetamine neurotoxicity

Abstract: Methamphetamine (METH) is a neurotoxic drug of abuse that damages the dopamine (DA) neuronal system in a highly delimited manner. The brain structure most affected by METH is the caudate–putamen (CPu) where long-term DA depletion and microglial activation are most evident. Even damage within the CPu is remarkably heterogenous with lateral and ventral aspects showing the greatest deficits. The nucleus accumbens (NAc) is largely spared of the damage that accompanies binge METH intoxication. Increases in cytoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 83 publications
1
43
0
Order By: Relevance
“…In support of this conclusion, although there are no studies on 4MM release, an in vitro study found the magnitude of DA release mediated by MeCa to be similar to METH, and greater than that of MEPH (Simmler et al, 2013). Consequently, a greater release in DA would promote the hypothesis that MeCa would induce greater neurotoxicity than MEPH and/or 4MM, since it has been shown in multiple studies that increasing the amount of DA available for release enhances METH toxicity (Kita et al, 1995, Thomas et al, 2008, 2009). Indeed, the depletion levels reported above support this hypothesis.…”
Section: Neurotoxicity Of 4-methylmethamphetamine and Methcathinonementioning
confidence: 67%
See 1 more Smart Citation
“…In support of this conclusion, although there are no studies on 4MM release, an in vitro study found the magnitude of DA release mediated by MeCa to be similar to METH, and greater than that of MEPH (Simmler et al, 2013). Consequently, a greater release in DA would promote the hypothesis that MeCa would induce greater neurotoxicity than MEPH and/or 4MM, since it has been shown in multiple studies that increasing the amount of DA available for release enhances METH toxicity (Kita et al, 1995, Thomas et al, 2008, 2009). Indeed, the depletion levels reported above support this hypothesis.…”
Section: Neurotoxicity Of 4-methylmethamphetamine and Methcathinonementioning
confidence: 67%
“…Whereas METH can release both cytosolic and vesicular stores, MEPH is only able to access the newly synthesized DA in the cytosol, limiting the amount of neurotransmitter it can release. Increasing the available pool of DA by either VMAT 2 inhibition or exogenous supplementation is known to potentiate the toxicity of METH (Thomas et al, 2008(Thomas et al, , 2009. Thus, it is feasible that the inability of MEPH to release DA via VMAT 2 would blunt its neurotoxic potential.…”
Section: Neurotoxicity Of 4-methylmethamphetamine and Methcathinonementioning
confidence: 99%
“…Vulnerability to MA has been linked to cytosolic content of DA. Thus, when blockade of DA storage occurs, MA toxicity is greater (Thomas et al 2009). Conversely, the blockade of de novo DA biosynthesis mitigates MA toxicity (Thomas et al 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Normalization of levels of a biologically important neurotransmitter could help normalize behavior. However, a practical safety issue is that, based on animal data, levodopa should probably not be administered at a time when residual MA is present in part because of possible damage to dopamine neurons (Thomas et al, 2009)-a consideration that could limit the use of levodopa in MA users who have a transient dopamine deficiency. We also suggest that, before any efficacy investigation, a safetytolerability clinical trial in MA users of levodopa in subjects who are in a controlled setting and are free of residual drug might be warranted.…”
Section: Discussionmentioning
confidence: 99%